Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.ymgme.2011.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analyses are instrumental in identifying the impact of mutations on holo and/or apo-forms and on the region(s) of alanine:glyoxylate aminotransferase variants associated with Primary Hyperoxaluria Type I

Abstract: Primary Hyperoxaluria Type I (PH1) is a disorder of glyoxylate metabolism caused by mutations in the human AGXT gene encoding liver peroxisomal alanine:glyoxylate aminotransferase (AGT), a pyridoxal 5′-phosphate (PLP) dependent enzyme. Previous investigations highlighted that, although PH1 is characterized by a significant variability in terms of enzymatic phenotype, the majority of the pathogenic variants are believed to share both structural and functional defects, as mainly revealed by data on AGT activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 35 publications
(44 reference statements)
4
50
1
Order By: Relevance
“…We compared the growth of yeast expressing mutant forms of AGT with their in vitro melting temperatures calculated in the holo-(bound to a PLP cofactor) or apo-forms, shown in Table 1. Previous work has shown that the apo-form of AGT unfolds in two steps indicative of two domains, which can be represented by two melting temperatures, T m1 and T m2 (Oppici et al 2012). Several mutant AGT variants show no defect in T m1 , but do not undergo a T m2 transition, indicative of a molecular defect confined to the second domain (Oppici et al 2012).…”
Section: Relationship Between Protein Stability and Growthmentioning
confidence: 98%
See 3 more Smart Citations
“…We compared the growth of yeast expressing mutant forms of AGT with their in vitro melting temperatures calculated in the holo-(bound to a PLP cofactor) or apo-forms, shown in Table 1. Previous work has shown that the apo-form of AGT unfolds in two steps indicative of two domains, which can be represented by two melting temperatures, T m1 and T m2 (Oppici et al 2012). Several mutant AGT variants show no defect in T m1 , but do not undergo a T m2 transition, indicative of a molecular defect confined to the second domain (Oppici et al 2012).…”
Section: Relationship Between Protein Stability and Growthmentioning
confidence: 98%
“…Previous work has shown that the apo-form of AGT unfolds in two steps indicative of two domains, which can be represented by two melting temperatures, T m1 and T m2 (Oppici et al 2012). Several mutant AGT variants show no defect in T m1 , but do not undergo a T m2 transition, indicative of a molecular defect confined to the second domain (Oppici et al 2012). In addition to alleles analyzed in Figure 1, we examined S158L-ma, W108R-mi, G350D-mi, and G161S-mi.…”
Section: Relationship Between Protein Stability and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression in mammalian cells is considered as the closest model of in vivo conditions and gives information on the expression level, intracellular stability and targeting of the AGT variants [17,28,35,40,[46][47][48][49][50]. On the other hand, the purification and characterization of the variants expressed in E. coli are suitable to dissect and quantify the effect of a mutation on the functional properties of AGT as well as on its secondary, tertiary and quaternary structures [11][12][13]17,18,35,36,[51][52][53][54][55][56][57][58]. Yeast and cell-free systems allow a rapid but semi-quantitative determination of the impact of each mutation on the intracellular activity, stability and assembly of the protein [37,53,54,59].…”
Section: A Comprehensive Analysis Of the Molecular And Cellular Effecmentioning
confidence: 99%